Improving Reading Literacy Through the Teaching At The Right Level Approach for Second Grade Students at SDN Inpres Pandai - Komalasari, Nur; Mulyadi, Mulyadi; Haryadi, Didit; Zulkifli, Zulkifli; Syarifuddin, Syarifuddin (Journal of Educational Sciences, 2025)
This study aims to improve the early reading literacy skills of second-grade students at SDN Inpres Pandai through the Teaching at the Right Level (TaRL) approach. The background of the research is the low reading ability among lower-grade primary students, indicating the need for instructional strategies aligned with students’ actual learning levels. This Classroom Action Research (CAR) was conducted in two cycles involving 20 students. Research instruments included an initial diagnostic assessment, reading tests, and observation sheets. Data were analyzed quantitatively by calculating average scores and percentage of achievement in each cycle. The findings showed consistent improvement in students’ reading performance. In the initial assessment, the average score was 52.05%, with most students struggling to recognize letters or read simple syllables. After the first cycle of TaRL implementation, the score increased to 66.26%, and in the second cycle, it significantly rose to 88.74%. In addition to academic gains, students showed increased confidence, participation, and interest in reading. The results suggest that the TaRL approach is effective in improving foundational reading skills. By adapting instruction to each student’s learning level, the method supports gradual and equitable learning progress, making it a promising strategy for early literacy development.